Risk factors in child maltreatment: a meta-analytic review of the literature - Stith, Sandra M.; Liu, Ting; Davies, L. Christopher; Boykin, Esther L.; Alder, Meagan C.; Harris, Jennifer M.; Som, Anurag; McPherson, Mary; Dees, J. E. M. E. G. (My University, 2012)
This review presents the results of a series of meta-analyses identifying the relative strength of various risk factors for child physical abuse and neglect. Data from 155 studies examining 39 different risk factors were included in the review. Large effect sizes were found between child physical abuse and four risk factors (parent perceives child as problem, parent anger, family conflict and family cohesion). Large effect sizes were also found between child neglect and six risk factors (child social competence, parent-child relationship, parent perceives child as problem, parent’s level of stress, parent’s level of anger, and parent’s self-esteem).
Keywords: Child maltreatment; Child physical abuse; Child neglect; Risk factors; Meta-analysis